ANALYSIS OF READING ABILITY IN CLASS II ELEMENTARY SCHOOL STUDENTS - Aulia Zahwa, Annisa (Lingustic, Literature and English Education, 2023)
The aim of this research was to determine the reading ability of class II students at SD Negeri 25 Lubuklinggau. The methods used in this research are descriptive research methods and qualitative research methods. The data sources for this research are class II students and teachers at SD Negeri 25 Lubuklinggau. The data collection techniques used are observations and questionnaires. This research data analysis includes stages consisting of data reduction, data presentation and drawing conclusions. Of the 18 class II students at SD Negeri 25 Lubuklinggau, 4 students, namely PT, RP, FAG and ME, experienced problems in the realm of reading. The problems experienced are: recognizing letters and distinguishing letters of the alphabet, spelling words, being lazy about reading texts to find answers and also lack of interest in reading both at school and at home.